Income convergence? Evidence of Non-linearity in the East Asian Economies : A Comment - Venus, Khim-Sen Liew; Yusuf, Ahmad (Universiti Malaysia Sabah (UMS), 2006)
This study demonstrates the usefulness of Kapetanois et al. (2003) test in differentiating the two stages of income convergence—long run convergence and catching up. A reexamination of the “Four Asian Dragons” economies, in which their income differentials with respect to Japan have been identified as non-linear stationary in Liew and Lim (2005), reveals that the economy of Hong Kong, Korea and Singapore are catching up, while Taiwan has yet to catch up, with the Japan economy.